Prenatal therapy in transient abnormal myelopoiesis: a systematic review - Tamblyn, JA; Norton, A; Spurgeon, L; Donovan, V; Bedford Russell, A; Bonnici, J; Perkins, K; Vyas, P; Roberts, I; Kilby, MD (BMJ Publishing Group, 2015)
Objective To systematically review current evidence regarding prenatal diagnosis and management of transient abnormal myelopoiesis (TAM) in fetuses with trisomy 21. A novel case of GATA1-positive TAM, in which following serial in utero blood transfusion clinical improvement and postnatal remission were observed, is included.